Modal control of seismic structures using augmented state matrix. - Lu, Lyan-Ywan (Earthquake engineering & structural dynamics.)
In conventional methods of modal control, the number of controllable structural modes is usually restrained by the number of sensors that feedback the structural signals. In this paper a modal control scheme where feedback gain is formulated in an augmented state space is proposed. The advantage of the proposed method is that it increases the number of the controllable modes without adding extra sensors. The method is verified experimentally by an earthquake simulation test with a full scale building model. The proposed modal control was also compared with the conventional ones in the test. For the building model tested, the performance of the proposed control with only one feedback signal can be as efficient as that of modal control with full state feedback.